Characterisation and stability of pigments extracted from sargassum binderi obtained from Semporna, Sabah - Wu, Hon Yip; Lim, Seng Joe; Wan Aida Wan Mustapha,; Mohamad Yusof Maskat,; Mamot Said, (Universiti Kebangsaan Malaysia, 2014)
This study was carried out to identify the pigment extracted from Malaysian brown seaweed, Sargassum binderi and its stability in various conditions. Pigments were extracted using methanol:chloroform:water (4:2:1, v/v/v), which is part of fucoidan extraction process, where the pigments were waste. Carotenoid and chlorophyll were found in the extract using UV-vis spectrophotometer (420 and 672 nm, respectively). Fucoxanthin was identified as the carotenoid present using HPLC, while its functional groups and structure were determined using FTIR and 1H NMR, respectively. The fucoxanthin-rich extract stability was tested on different pH (pH1-13), light exposure (dark and light) and storage temperature (4ºC, 25ºC and 50ºC). The stability tests showed that it was most stable at pH5-7, stored in dark condition and at the storage temperature of 4ºC and 25ºC. The fucoxanthin-rich extract from Sargassum binderi has potential to be applied as bioingredient and functional food as it is stable in normal storage conditions.